The making of an influenza pandemic - Van-Tam, Jonathan (Henry Stewart Talks, 2013)
Classification, structure and nomenclature, The history of influenza, The history of human pandemics and recent pandemic threats, Pandemic versus seasonal influenza, Antigen recycling, Relation between animal and human influenza, Antigen shift, Modes of pandemic emergence, Characteristics of human pandemics, Summary, Further reading